Perinatal outcomes in women living with HIV‐1 and receiving antiretroviral therapy—a systematic review and meta‐analysis - Shiri Shinar; Swati Agrawal; Michelle Ryu; Sharon Walmsley; Lena Serghides; Mark H. Yudin; Kellie E. Murphy (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Antiretroviral therapy‐naïve pregnant women living with HIV are at an increased risk for adverse pregnancy outcomes. It remains controversial whether this risk persists with antiretroviral therapy. We conducted a systematic review and meta‐analysis to evaluate whether pregnant women living with HIV and receiving antiretroviral therapy antenatally, are at an increased risk of adverse outcomes compared with HIV‐negative controls. Material and methods We searched MEDLINE, Embase, International Pharmaceutical Abstracts, EBM Reviews, PubMed (non‐MEDLINE records), EBSCO CINAHL Complete, Clarivate Web of Science, African Index Medicus, LILACS and Google Scholar for all observational studies comparing pregnant women living with HIV on antiretroviral therapy with HIV‐negative controls from 1 January 1994 to 10 August 2021 with no language or geographic restrictions. Perinatal outcomes included preterm birth (PTB), low birthweight, small‐for‐gestational age and preeclampsia. Using a random‐effects model we pooled raw data to generate odds ratio (OR) with 95% confidence intervals (CI) for each outcome. Sub‐analyses for high and low resource countries and time of antiretroviral therapy initiation were performed. This systematic review and meta‐analysis is registered with PROSPERO, number CRD42020182722. Results Of the 7900 citations identified, 27 were eligible for analysis (12 636 pregnant women living with HIV on antiretroviral therapy and 7 812 115 HIV‐negative controls). ORs (95% CI) of PTB (1.88 [1.63–2.17]), small‐for‐gestational age (1.60 [1.18–2.17]) and low birthweight (2.15 [1.58–2.92]) were significantly higher in pregnant women living with HIV than in HIV‐negative women, while the risk of preeclampsia (0.86 [0.57–1.30]) was comparable. The risk of PTB and low birthweight was higher in both high resource and low resource countries, while the risk of small‐for‐gestational age was higher only in the former. Preconceptional antiretroviral therapy was associated with a higher risk of PTB compared with antenatal initiation. Conclusions Pregnant women living with HIV on antiretroviral therapy have an increased risk of PTB, low birthweight and small‐for‐gestational age in high resource countries, as well as PTB and low birthweight in low income countries compared with HIV‐negative controls.